Potential of pseudomonas aeruginosa environmental isolates for biofilm formation - Mile Božić; Vera Raičević (Zaštita Materijala)
Biofilm formation is one of the main characteristic of Pseudomonas aeruginosa strains. This ability provide bacteria to survive in different, usually restrictivesss environmental conditions. In the same time, biofilm forming is a risk in a many field of industry, mainly in food industry. It is known that diverse P. aeruginosa strains from various environmental sources have different potention to form biofilms. In this paper it is examinated the potention to form biofilm four isolates of P. aeruginosa and based of this results, tested isolates have classificated into four groups. Biofilm formation tested in microtitar plates during the 24 hours at changed conditions of temperature (37°C and 22°C), pH (6 and 7) and concentration of NaCl (1% and 2%). Obtained results have shown that isolated P. aeruginosa have unsimilar ability to form biofilms. Biomass of formed biofilm was greater at 22°C than at 37°C. Also, acid conditions and higher concentration of salt had no inhibitory effect to biofilm forming process.